Assessment of Postural effect on Work Related Musculoskeletal Disorders and Back Muscle Fatigue among the Goldsmiths of India - Tirthankar Ghosh (Occupational Health and Safety Society of Nepal, 2017)
Background: Musculoskeletal disorders (MSD) may be defined as injuries and disorders of the muscles, nerves, tendons, ligaments, joints, cartilage and spinal disc. This may occur due to improper physical work activities or appalling workplace conditions. Awkward or extreme postures are less efficient than posture keep joints near the center of their range of motion. Objective: The objective of the current study was to assessment of postural effect on work related musculoskeletal disorders and back muscle fatigue among the goldsmiths of India. Methods: In this current study, the experiment was performed on 100 male goldsmiths. A detailed questionnaire study on discomfort feeling was done and analysis of body posture by Rapid Upper Limb Assessment was done to evaluate the work stress during their job. Electromyographic activity was collected from ten major trunk muscles sites which consist of right and left muscle. Result: From the analysis, it was revealed that musculoskeletal disorders were the major problem of the goldsmiths. Moreover questionnaire study revealed that most of the workers were affected by pain at Neck (80%), Low back (91%), Wrist (45%), Shoulder (20%). Decreased in RMS and MedF of all the ten major trunk muscles were observed at the end of the every work cycle, which indicating that muscular fatigue was induced by the Gold Smiths tasks. Conclusion: From this study it can be concluded that the goldsmiths are working in awkward and forward bending postures for prolonged period of time with the potential risks of musculoskeletal disorders primarily affecting the low-back and neck region of the body. This can be attributed by the improper design of the workstation